Ecological Aspects of Dwelling Position For A previous Case of Kala – azar in South of Baghdad , Iraq - Salman, S. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This is a contribution to study the situation of a dwelling of previous case of kala- azar in the endemic area (AL-Mahmodiya/ AL-Rasheed district) about 25 km south of Baghdad.  In order to assess the possible ecological causes of the incidence and the prevalence of visceral leishmaniasis, in one of the well-known foci of the disease in the central region of Iraq. It was found that the human dwelling position and ecological factors affect the infection with this disease.